Analisis Kecakapan Abad 21: Collaboration and Communication Skills Siswa Melalui Penerapan Discovery Learning - Adif Fatus Syarofah; Eny Hartadiyati; Joko Siswanto; Novanto Eka Wahyu (Journal on Education, 2023)
This study aims to determine the 21st century skills in the form of culinary skills and communication skills of class X students of SMK N 6 Semarang through the application of discovery learning models. This research is a quantitative descriptive research with a one shot case study research design. The population of this research is class X Culinary SMK N 6 Semarang. Sampling used a purposive sampling technique, namely class X Culinary 1 SMK N 6 Semarang. The skills assessment instrument used in this study was an observation sheet consisting of an observation sheet for collaboration skills and an observation sheet for communication skills. Based on the data analysis that has been carried out, the results show that the skill skills of students in class X culinary 1 at SMK N 6 Semarang are achieved in the very high category, so that it can be interpreted that the application of discovery learning is capable of reaching the age of the 21st century, namely skills skills and communication skills.